Bobcat occupancy, tree islands, and invasive Burmese pythons in an Everglades conservation area - Buckman, Katherine M.; D'Acunto, Laura E.; Romañach, Stephanie S.; Taylor, Rachel M.; Dorn, Nathan J. (The Journal of wildlife management, 2024)
Bobcats (Lynx rufus) are terrestrial mammals that also inhabit tree islands (i.e., topographically elevated patches of forested land) embedded in the subtropical Everglades wetlands, which serve as a dry refuge habitat during the wet season in this region of Florida, USA. The Comprehensive Everglades Restoration Plan seeks to restore Everglades water flow to pre‐drainage conditions, but little is known about how water levels or other landscape‐level factors may influence mammalian occurrence, such as bobcats, on the tree islands in this ecosystem. We used game camera records and occupancy modeling to test for effects of static habitat variables and dynamic hydrologic variables. We hypothesized that deep water levels would limit the accessibility of tree islands to bobcats; therefore, we predicted that bobcat occupancy would decline with higher water levels. We also tested for the effect of an expanding invasive snake (i.e., Burmese python [Python molarus bivittatus]) using output from a model constructed to predict density and spread of Burmese pythons across southern Florida. We hypothesized that increases in Burmese pythons on the landscape would influence the food resources of bobcats, resulting in reduced bobcat occupancy at higher predicted densities of pythons. We built detection histories using 1,855 bobcat images from game cameras set on 87 tree islands in an Everglades conservation area from 2005–2019. Bobcat occupancy was significantly diminished when predicted Burmese python densities exceeded approximately 3 Burmese pythons/km2. Bobcat occupancy probability also increased with tree‐island density around the focal tree island. Although water depth and hydroperiod surrounding tree islands appeared in our top 3 candidate models, the hydrologic variables had weak effects on bobcat occupancy. Our results suggest that while hydrologic dynamics may play a role, the invasive Burmese python has stronger influences on bobcat occupancy of tree islands in this Everglades conservation area. We used bobcat detections across 87 tree islands in an Everglades conservation area from 2005–2019 to test hypotheses about bobcat use of tree islands relative to landscape covariates, hydrologic covariates, and predicted spatiotemporal Burmese python densities. Bobcat occupancy was significantly diminished when predicted Burmese python densities exceeded ~3 Burmese pythons/km2, and bobcat occupancy probability increased with increasing tree‐island density around the focal tree island.